Foreign Direct Investment in the World Economy - Graham, Edward (IMF Working Papers; Working Paper ;, 1995)
The role of foreign direct investment (FDI) in international capital flows is examined. Theories of the determinants of FDI are surveyed, and the economic consequences of FDI for both host (recipient) and home (investor) nations are examined in light of empirical studies. Policy issues surrounding possible negotiation of a 'multilateral agreement on investment' are discussed.